Cognitive and higher-level contributions to illusory self-motion perception (“vection”): does the possibility of actual motion affect vection? - Riecke, Bernhard E. (Japanese Journal of Psychonomic Science, 2009)
Large-field moving visual stimuli have long been known to be capable of inducing compelling illusions of self-motion (“vection”) in stationary observers. Traditionally, the origin of such visually induced self-motion illusions has been attributed to low-level, bottom-up perceptual processes without much cognitive/higher-level contribution. In the last years, however, this view has been challenged, and an increasing number of studies has investigated potential higher-level/cognitive contributions. This paper aims at providing a concise review and discussion of one of these aspects: Does the cognitive framework of whether or not actual movement is possible affect illusory self-motion? Despite a variety of different approaches, there is growing evidence that both cognitive and perceptual information indicating movability can facilitate self-motion perception, especially when combined. This has important implications for our understanding of cognitive/perceptual contributions to self-motion perception as well as the growing field of self-motion simulations and virtual reality, where the need for physical motion of the observer could be reduced by intelligent usage of cognitive/perceptual frameworks of movability.
Keywords: Riecke; Riecke_2009; bernhard-riecke; iSpaceWeb; journalPaper; vection